Antibacterial Effect of Onion‘s Infusion and Garlic‘s Infusion on Escherichia Coli Isolated from Urine Samples - Salman, Ahmed Sami (Journal of Biomedicine and Biochemistry, 2022)
Introduction many searchers studies properties of Onion extract and garlic extract,but they do not study infusion effect of garlic and onion against bacteria.The Aim to know antibacterial activity of Onion‘s Infusion and Garlic‘s Infusion.Methodology searcher prepared garlic infusion for many periods, and onion infusion for many periods also, and study antibacterial activity against Escherichia Coli Isolated from Urine Samples.Results : thirty urine samples were collected to detect the presence of E. coli and the study found that (26) samples contained Escherichia Coli bacteria at a rate of (86.66%) through phenotypic and microscopic diagnosis and then diagnosed with Vitek, infusion garlic and onion separately for different periods of time and with different concentrations, and it was found that the highest concentration of 100ppt was more effective on inhibiting the growth of bacteria, the study also tested the synergistic and antagonistic activity of both infusions on the inhibition of bacterial growth.Conclusion The activity of preventing the growth of bacteria was enhanced by prolonging the infusion of garlic oronions. Additionally, neither a synergistic nor an inhibitory effect is related to concentration changes.